Does insurance promote economic growth: A comparative study of developed and emerging/developing economies - Sajid Mohy ul din; Arpah Abu-Bakar; Angappan Regupathi (Cogent Economics & Finance, 2017)
This paper examines the relationship between insurance and economic growth in 20 countries for the period 2006-2015. Insurance activity is measured through three distinctive proxies such as net written premiums, penetration and density. The Hausman statistics confirmed that fixed effect model is appropriate for this data-set. This study found a positive and a significant relationship between life insurance, measured through net written premiums and density, and economic growth for developed countries while the same is true for developing countries when insurance is measured through penetration proxy. The results also reveal that non-life insurance has statistically significant, for all three proxies, relationship with economic growth for developing countries whereas, in case of developed countries, the results are only significant when insurance density is used as a proxy for insurance. Moreover, the role of non-life insurance is more significant for developing countries as compared to developed countries.
Keywords: 330; insurance; life insurance; non-life insurance; economic growth